Trade, climate change, and climate-smart agriculture - Haile, Beliyou; Azzarri, Carlo; Koo, Jawoo; De Pinto, Alessandro (International Food Policy Research Institute, 2017)
Chapter 5 focuses on the role of CSA in the context of trade flows in three regional economic communities (RECs): the Economic Community of West African States (ECOWAS), the Common Market for Eastern and Southern Africa (COMESA), and the Southern African Development Community (SADC). Likely agroclimatic changes will not only impact agriculture but also countries’ ability to fully benefit from regional and international trade, especially when rainfed-based agricultural commodities dominate trade flow. The authors find that CSA practices have the potential to mitigate climate-induced risks in agricultural production and food security through increased and less volatile agricultural trade flows.